Interpreting flora motif in the Karmawibhangga relief: A Buddhist iconography of Borobudur - Fauziah, Fauziah; Maryanto, Ibnu; Mundayat, Aris Arif; Ashari, Hidayat; Rusdianto, Rusdianto; Wibowo, Dony Satryo; Sulistyadi, Eko; Sujarwo, Wawan (Ethnobotany Research and Applications, 2026)
Background: Borobudur Temple in Indonesia is one of the world's UNESCO World Heritage sites, known for its beautiful architecture, with reliefs, sculptures, and carved stone. The Karmawibhangga reliefs, hidden at the temple’s foot, uniquely illustrate the law of karma through cause-and-effect vignettes. Despite their fragmented preservation, these reliefs reveal flora as active narrative elements, though their species and symbolic roles remain understudied. Methods: This study employed a multidisciplinary approach to analyse the flora motifs in the 160-panel Karmawibhangga. Flora identification was conducted through a morphological approach, comparing the habitus, roots, stems, leaves, flowers, and fruits, and analysing relief as a discourse that combines social and ecological dimensions in an interpretive manner. Narrative structure was examined through intratextual, intertextual, and extratextual. Results: This study identifies 39 plant species—dominantly Mangifera indica (mango), Calophyllum inophyllum (tamanu), and sacred composites such as the Kalpataru—through morphological analysis and cross-referencing with the Javanese flora and Buddhist texts. Results reveal intentional species selection: mango groves reflect abundance and meditation sites, while tamanu’s riverbank habitat symbolises karmic dissemination. Spatial analysis shows that the flora is arranged hierarchically (middle > left > middle > right panels) and viewed from distinct angles (frontal, aerial, and ground-level), reinforcing narrative themes. The Kalpataru, blending Ficus religiosa (Bodhi tree), Garcinia mangostana (mangosteen), and Nelumbo nucifera (sacred lotus), exemplifies sacred hybridity, strategically placed in the north-east panels associated with heavenly realms (svargga). Agricultural depictions (taro, rice, millet) further intertwine subsistence with cosmology, as millet’s north-facing panels align with Buddhist celestial symbolism. The study underscores flora as semiotic devices that encode karmic principles through ecological realism and artistic convention. Conclusion: The Karmawibhangga reliefs depict flora as a dynamic semiotic system. By integrating naturalistic details with doctrinal symbolism, these reliefs can articulate a holistic vision of life's meaning. Keywords: Borobudur, Buddhist iconography, Flora symbolism, Javanese ecology, Karmawibhangga reliefs